Pemanfaatan Daun Sirih (Piper betle L.) untuk sabun cair cuci tangan di kampung Eduwisata Alam Sungai Masjid Kota Dumai - Ninik Nihayatul Wahibah; Nurhasanah Putri Rakhman; Tania Aisyah Rinaldi; Maharani Anugerah Sirajuddin; Tasha Nurul Amalia; Raisya Melfa; Putri Thassya Novanka Efendi; Khoirunnisa Aprilia (Unri Conference Series: Community Engagement, 2022)
Betel leaf plants (Piper betle L.) are medicinal plants containingchemical compound that can be used for varied purpose. These plants are easily found in Kampung Eduwisata Sungai Masjid Dumai as artificial plants in their house yard. They usually use the leaves only for cultural ceremony. Therefore, our community service programme aimed to enhance knowledge and skills in utilizing betel leaf natural handsoap. Antiseptic hand soap from betel leaf is used to meet the need for hand soap that is safe and friendly to the skin.Our partner of the programme was high school students in Kampung Eduwisata Sungai Masjid Dumai. This activity was carried outby training how to make hand washing soap with betel leaves as a basic ingredient.Result of this programme showed that our partner were enthusiastic and active in the discussion session. As a result of this activity, there was an increase in the skills of participants in making antiseptic hand soap from betel leaves as indicated by result of questionnaire.